2019
DOI: 10.1186/s40360-018-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

In vitro wound healing of tumor cells: inhibition of cell migration by selected cytotoxic alkaloids

Abstract: BackgroundCell migration is involved in several pathological processes such as tumor invasion, neoangiogenesis and metastasis. Microtubules are needed in directional migration.MethodsTo investigate the effects of microtubule-binding agents (paclitaxel, vinblastine, colchicine, podophyllotoxin), benzophenanthridine alkaloids (sanguinarine, chelerythrine, chelidonine) and other anti-tumor drugs (homoharringtonine, doxorubicin) on cell migration, we performed the in vitro wound healing assay. The interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(60 citation statements)
references
References 48 publications
5
52
0
3
Order By: Relevance
“…Wound healing assay on cancer cell was carried out according to previously reported method 26 . A549 lung cancer cells were cultured at a density of 1.5 × 10 6 cells/well for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Wound healing assay on cancer cell was carried out according to previously reported method 26 . A549 lung cancer cells were cultured at a density of 1.5 × 10 6 cells/well for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the potential of 1 to suppress migration of MDA-MB-231 cancer cells indicates that this compound may prove as an efficient molecule in inhibiting the metastasis of cancer cells in vitro . 26 To clarify the role of 1 in cancer cell apoptosis and chemoresistance, we examined cell viability and apoptosis rate using 4′,6-diamidino-2-phenylindole (DAPI) staining and cell cytotoxicity assay [sulforhodamine B (SRB)]. 27 Our data demonstrated that 1 overexpression was able to inhibit cell viability, which was downregulated by 1 treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The wound healing and migration experiment offer the opportunity to observe cell migration, which plays an important role in several processes in tumor development, such as neoangiogenesis and metastasis. In cell culture as well as in vivo, microtubules are required for cell migration [ 38 ]. In this regard, it is important to determine the efficacy of microtubule-stabilizing agents such as PCX in wound-healing assays.…”
Section: Resultsmentioning
confidence: 99%